Teaching and Learning About Islam in Middle School Social Studies Classrooms. Issue 4 (1st October 2020) - Fitzpatrick, Colleen; Friedman, Adam
Abstract: This multiple case study explores how two middle school social studies teachers enact a district mandated unit on the Islamic Empire. Using Cunningham's division of influences on teacher practices, we analyzed the data for the various factors that impacted how these teachers enacted a unit on Islam. Analysis of the data highlighted how one teacher attempted, and somewhat failed, to engage students with the relevancy of the unit due to the structural factors of the school in which he worked, while the other teacher enacted a unit that focused primarily on memorization of vocabulary words.